Chemical compositions of sulfate and chloride salts over the last termination reconstructed from the Dome Fuji ice core, inland Antarctica. Issue 24 (16th December 2014) - Oyabu, Ikumi; Iizuka, Yoshinori; Uemura, Ryu; Miyake, Takayuki; Hirabayashi, Motohiro; Motoyama, Hideaki; Sakurai, Toshimitsu; Suzuki, Toshitaka; Hondoh, Takeo
Abstract The flux and chemical composition of aerosols impact the climate. Antarctic ice cores preserve the record of past atmospheric aerosols, providing useful information about past atmospheric environments. However, few studies have directly measured the chemical composition of aerosol particles preserved in ice cores. Here we present the chemical compositions of sulfate and chloride salts from aerosol particles in the Dome Fuji ice core. The analysis method involves ice sublimation, and the period covers the last termination, 25.0–11.0 thousand years before present (kyr B.P.), with a 350 year resolution. The major components of the soluble particles are CaSO4, Na2SO4, and NaCl. The dominant sulfate salt changes at 16.8 kyr B.P. from CaSO4, a glacial type, to Na2SO4, an interglacial type. The sulfate salt flux (CaSO4 plus Na2SO4) inversely correlates with δ18O in Dome Fuji over millennial timescales. This correlation is consistent with the idea that sulfate salt aerosols contributed to the last deglacial warming of inland Antarctica by reducing the aerosol indirect effect. Between 16.3 and 11.0 kyr B.P., the presence of NaCl suggests that winter atmospheric aerosols are preserved. A high NaCl/Na2SO4 fraction between 12.3 and 11.0 kyr B.P. indicates that the contribution from the transport of winter atmospheric aerosols increased during this period.